Kultur Kelas Menengah dan Kelahiran ICMI - Saiful Mujani (Studia Islamika, 1994)
Robert W. Hefner and Mitsuo Nakamura argue that the establishment of the Ikatan Cendikiawan Muslim se-Indonesia (ICMI), or the Muslim Intellectual Society of Indonesia, is a manifestation of the rising Muslim middle class that the cultural foundation of the Muslim middle class and the ICMI is 'renewal Islam' or Islamic neomodernism, which stresses the modern spirit: tolerant, pluralist, moderate, democratic, etc.DOI: 10.15408/sdi.v1i1.872